Databases on Modern Networks: A Decade of Research that now comes into Practice - Lerner, Alberto; Binnig, Carsten; Cudré-Mauroux, Phillipe; Hussein, Rana; Jasny, Matthias; Jepsen, Theo; Ports, Dan R. K.; Thorup, Lasse; Ziegler, Tobias (2023 Very Large Data Bases, 2023)
Modern cloud networks are a fundamental pillar of data-intensive applications. They provide high-speed transaction (packet) rates and low overhead, enabling, for instance, truly scalable database designs. These networks, however, are fundamentally different from conventional ones. Arguably, the two key discerning technologies are RDMA and programmable network devices. Today, these technologies are not niche technologies anymore and are widely deployed across all major cloud vendors. The question is thus not if but how a new breed of data-intensive applications can benefit from modern networks, given the perceived difficulty in using and programming them. This tutorial addresses these challenges by exposing how the underlying principles changed as the network evolved and by presenting the new system design opportunities they opened. In the process, we also discuss several hard-earned lessons accumulated by making the transition first-hand.
Tutorial